Sarapan Pagi dan Konsentrasi Belajar Anak Sekolah Dasar Negeri 02 Balerejo Kabupaten Madiun - kurniasih, erwin (JPKM: Jurnal Profesi Kesehatan Masyarakat, 2020)
Breakfast is important and has an impact on physical health conditions, especially for school age children. Students in Grade 4 and 5 of SD Negeri 02 Balerejo had a habit of restless class time because of hunger. This study aimed to determine the relationship between breakfast and the learning concentration of grade 4 and 5 students at SD Negeri 02 Balerejo, Madiun Regency in 2019. This study used Cross sectional research design. The population in this study were 40 students of grade 4 and 5 SD Negeri 02 Balerejo. Sampling in this study used simple random sampling technique in order to obtain a sample of 36 children. Collecting data in this study used interviews and observation sheets. Analysis of research data included univariate analysis and bivariate analysis using the chi square test. The results showed that most of the 52.8% of respondents did not eat breakfast and most of the 66.7% of respondents with poor concentration levels of learning. Based on the results of statistical analysis, the value of p = 0.024 and PR = 3.75 means that there was a significant relationship between breakfast and the concentration level of student learning. For this reason, it is hoped that all parties, both schools and parents, can make efforts to get the kids breakfast used to before leaving for school.